1998
DOI: 10.1002/(sici)1098-2280(1998)31:3<263::aid-em8>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response studies of the induction of hyperdiploidy and polyploidy by diethylstilbestrol and 17β-estradiol in cultured human lymphocytes using multicolor fluorescence in situ hybridization

Abstract: Diethylstilbestrol (DES) and 17β‐estradiol (E2) are known inducers of aneuploidy and polyploidy in vivo and in vitro. Isolated human lymphocytes were treated with the stilbene estrogen DES (0.05–50 μM) and the steroid estrogen E2 (0.05–75 μM) in culture. Multicolor fluorescence in situ hybridization (FISH) with DNA probes for the centromere and adjacent heterochromatin regions of chromosomes 1, 9, and 16 was used to detect hyperdiploidy, polyploidy, and chromosomal breakage affecting these chromosomes. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The present study confirms these earlier findings and notes aneugenic effects as well. Aneuploidy and polyploidy reflect delayed or halted cell cycle progression, which may interrupt normal cell proliferation or trigger improper apoptosis in developing embryos, and is linked to stillbirths and birth defects (Oshimura & Barrett, 1986;Schuler et al, 1998). TPT was reported to induce aneuploidy in cultured human lymphocytes by altering spindle function (Jensen et al, 1991).…”
Section: Apoptosis and Aneuploidymentioning
confidence: 99%
“…The present study confirms these earlier findings and notes aneugenic effects as well. Aneuploidy and polyploidy reflect delayed or halted cell cycle progression, which may interrupt normal cell proliferation or trigger improper apoptosis in developing embryos, and is linked to stillbirths and birth defects (Oshimura & Barrett, 1986;Schuler et al, 1998). TPT was reported to induce aneuploidy in cultured human lymphocytes by altering spindle function (Jensen et al, 1991).…”
Section: Apoptosis and Aneuploidymentioning
confidence: 99%
“…The testosterone derivatives could become aromatic and convert to 17 β ‐estradiol, which induces various chromosomal and genetic lesions, including aneuploidy, chromosomal aberrations, gene amplification, and microsatellite instability in cells in culture and/or in vivo and gene mutations in several cell test systems (Liehr, ). Some sex hormones such as β ‐estradiol, diethylstilbestrol and estriol (among others) have shown capacity to produce alterations in chromosome number (Wheeler et al , ; Schuler et al , ) and micronucleus induction by mitotic disturbances has been described (Eckert and Stopper, ; Fischer et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…From the present study it is evident that the nandrolone induced genotoxic effects on peripheral blood, liver, bone marrow, brain and testicle cells of mice when tested using the comet assay, and induced clastogenic effects, as observed in the micronucleus test. Some studies showed that AAs do not induce gene mutation in classical bacterial and mammalian mutation assays, but at the chromosomal level several studies have reported that this similar hormones induces chromosomal breaks or aberrations (Schuler et al , ; Fischer et al , ; Torres‐Bugarín et al , ; among others).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although estrogens have been clearly shown to be carcinogenic in human and animal models, the mechanism of action by which estrogenic compounds induce cancer is not well understood. Studies have demonstrated that DES induces morphologic and neoplastic transformation, as well as, aneuploidy in both in vivo and in vitro models (9,10,26,27) . Experimental evidence also suggests that DES is able to induce aneuploidy by binding to tubulin and microtubules and by subsequently interfering with spindle formation (28,29) .…”
Section: Discussionmentioning
confidence: 99%